Modulation of fetoplacental growth, development and reproductive function by endocrine disrupters - Basak, Sanjay; Varma, Saikanth; Duttaroy, Asim K. (Frontiers in Endocrinology, 2023)
Maternal endocrine homeostasis is vital to a successful pregnancy, regulated by several hormones such as human chorionic gonadotropin, estrogen, leptin, glucocorticoid, insulin, prostaglandin, and others. Endocrine stress during pregnancy can modulate nutrient availability from mother to fetus, alter fetoplacental growth and reproductive functions. Endocrine disrupters such as bisphenols (BPs) and phthalates are exposed in our daily life's highest volume. Therefore, they are extensively scrutinized for their effects on metabolism, steroidogenesis, insulin signaling, and inflammation involving obesity, diabetes, and the reproductive system. BPs have their structural similarity to 17-β estradiol and their ability to bind as an agonist or antagonist to estrogen receptors to elicit an adverse response to the function of the endocrine and reproductive system. While adults can negate the adverse effects of these endocrine-disrupting chemicals (EDCs), fetuses do not equip themselves with enzymatic machinery to catabolize their conjugates. Therefore, EDC exposure makes the fetoplacental developmental window vulnerable to programming in utero. On the one hand prenatal BPs and phthalates exposure can impair the structure and function of the ovary and uterus, resulting in placental vascular defects, inappropriate placental expression of angiogenic growth factors due to altered hypothalamic response, expression of nutrient transporters, and epigenetic changes associated with maternal endocrine stress. On the other, their exposure during pregnancy can affect the offspring's metabolic, endocrine and reproductive functions by altering fetoplacental programming. This review highlights the latest development in maternal metabolic and endocrine modulations from exposure to estrogenic mimic chemicals on subcellular and transgenerational changes in placental development and its effects on fetal growth, size, and metabolic & reproductive functions.